Management and outcome of native joint septic arthritis: a nationwide survey in French rheumatology departments, 2016–2017. Issue 11 (12th July 2022) - Richebé, Pauline; Coiffier, Guillaume; Guggenbuhl, Pascal; Mulleman, Denis; Couderc, Marion; Dernis, Emanuelle; Deprez, Valentine; Salliot, Carine; urien, Saik; Brault, Rachel; Ruyssen-Witrand, Adeline; Hoppe, Emmanuel; et al.
Abstract : Objectives: To describe current management and outcome of native joint septic arthritis (NJSA) in French rheumatology departments. Methods: For this retrospective, nationwide multicentric study, 127 French rheumatology departments were contacted to report up to 12 cases of NJSA that occurred between 1 January 2016 and 31 December 2017. Characteristics, diagnosis procedures, therapeutic management and outcome were recorded. Results: Overall, 362 patients were included (mean age 64.0±18.6 years, median Charlson comorbidity index 3.5 (0–14)). Knee was the most frequent site (n=160 (38.9%)), and Staphylococcus sp (n=185 (51.4%)), the most frequent pathogen. All patients received antibiotics for a mean duration of 46.8 (±22.0) days, including intravenous route for a mean of 17.2 (±15.4) days. Management was heterogeneous. Surgical procedure was performed in 171 (48.3%), joint immobilisation in 128 (43.8%). During follow-up, 91 (28.3%) patients have had serious complications and 28 (9.2%) of them died. Factors associated with 1-year mortality were age (OR 1.08, 95% CI 1.04 to 1.13; p<0.001), Charlson's index (OR 1.30, 95% CI 1.06 to 1.58; p=0.012), presence of bacteraemia (OR 4.02, 95% CI 1.35 to 11.99; p=0.008), antibiotic use in the previous 3 months (OR 3.32, 95% CI 1.11 to 9.87; p=0.029) and Staphylococcus aureus NJSA compared with Streptococcus sp. NJSA (OR 7.24, 95% CI 1.26 to 41.68, p=0.027). The complete recovery with no adverse joint outcome at 1 year was observed in n=125/278 patients (55.0%). Conclusion: Prognosis of NJSA remained severe with a high rate of morbimortality. Its management was very heterogeneous. This study highlights the importance of the new French recommendations, published after the completion of the study, in order to facilitate NJSA management.